Cardiac remodeling: Serial analysis and indexes for early detection of ventricular dysfunction - Mendes, Olga De Castro [UNESP] (2010)
Background: Supravalvar aortic stenosis (SVAS) is used to study overload-induced cardiac remodeling (CR). In this model, neither CR behavior since beginning stage nor the best parameters to identify ventricular dysfunction are clearly stated. Objective: 1) Characterizing, early and evolutively, morphological and functional modifications during CR in rats with SVAS and 2) identifying the most sensitive index for detecting the moment when the diastolic and systolic dysfunction first appeared in the left ventricle (LV). Methods: Wistar Rats were divided into two groups - control (CG, n= ) and SVAS (SVASG, n= 4) - and studied in post-surgical 3rd, 6 th, 12th and 18th weeks. Hearts were analyzed by means of an echocardiogram (ECHO). Results: By the end of the experiment, ratios between the LV, right ventricle and atria and the final body weight were increased in the SVASG. The ECHO showed that the left atrium underwent significant remodeling from the 6th on. The percent of endocardial shortening underwent significant drop as of the nd week and the percent of, as of the 8th week, in the SVASG. The ratio between E- wave and A-wave (E/A) was higher in CG compared to the SVASG in all events analyzed. Conclusions: During the remodeling process, the left ventricle of rats with SVAS presented concentric hypertrophy, early diastolic dysfunction and improvement of systolic function, with posterior performance deterioration. Besides this, the study found out the most sensitive echocardiographic indexes for detecting systolic and diastolic dysfunction are, respectively, the ratio E/A and the percent of endocardial shortening.